Teaching -Learning Process as a Strategy to Recover and Strengthen the Shuar Culture - Asqui, Jeferson Dario Crespo; Quichimbo, Danilo Marcelo Diaz; Chamba, Bolívar Dionicio Granda; Maliza, Veronica de Lourdes Lligalo (Journal of Ecohumanism, 2024)
This study examines the impact of the teaching-learning process on the preservation of the Shuar culture in Ecuador, specifically in the Morona Santiago Support Center. The main objective is to analyze how the Bilingual Intercultural Educational Model (MOSEIB) contributes to the rescue of the Shuar cultural identity among children and young people. The methodology is quantitative and descriptive, using surveys to obtain data on the perception and experiences of teachers and students. The population includes 51 people, including 33 teachers and 18 students, who answered questions about the use of cultural resources in the classroom and the relevance of Shuar customs as myths, legends, and mother tongue. The results indicate a positive acceptance of the MOSEIB model, as both students and teachers express that teaching based on the Shuar culture reinforces their identity. A high percentage of students enjoy cultural activities and value the use of traditional language and dress. In conclusion, the Intercultural Bilingual Educational Model has a positive impact, promoting the continuity of Shuar traditions and generating a space of respect and appreciation of their culture both in the educational field and in daily life.